TINJAUAN TENTANG PARTISIPASI MASYARAKAT DALAM MENDUKUNG PEMBANGUNAN DI DESA SANGATTA UTARA KABUPATEN KUTAI TIMUR - Salasiah dan Hasbiah (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2020)
This research is based on community participation in participation indeveloping their village, both in mind participation, participation ofpersonnel, participation of expertise, participation of goods and moneyparticipation.The purpose of this study is to find out how the communityparticipation in the implementation of regional development in the village ofNorth Sangatta Kecamatan Sangatta North East Kutai Regency. Type ofresearch or explanation used is descriptive qualitative used to describeresearch variables. Types of data used, observation interviews, anddocumentation.With the implementation of research in North Sangatta village,Kecamatan Sangatta Utara, East Kutai Regency is expected to give an ideahow community participation in the implementation of regional developmentso that the concept of participatory development that has been applied can bemeasured and can be used as a reference in subsequent research related to thesubstance of the discussion.From the results of the research that has been carried out, it can beillustrated that the application of participatory development in the village ofNorth Sangatta if referring to the musrenbang results that have been recordedin BAPPEDA of East Kutai Regency, the result obtained is that although in theplanning phase the community still participates, but at the stage ofimplementation of community participation which is expected to exist, was notfound at all, because at the stage of project implementation carried out by thewinning contractor. However, if we refer to the development projectimplemented by the empowerment program running in the village of SangataUtara, mainly funded from the village allocation fund, the research found that the enthusiasm of the community to participate in every stage of developmentcarried out from the planning, implementation, until the project evaluationphase is very high. This can be concluded in the implementation stage thereare still many things that must be addressed